Hubungan Kecerdasan Emosi dengan Perilaku Seksual Pranikah pada Remaja SMA Negeri 3 Surakarta - Anggara, Puji Astuti; ., Sumardiyono; Murti, Bhisma (Nexus Kedokteran Komunitas, 2012)
Background: High emotional intelligence can prevent adolencents from deviant behaviour, particullary premarital sexual behavior. This study aims to prove that high emotional intelligence can reduce premarital sexual behavior. Methods: This study is an analytical observational research using cross sectional approach. This study had been done in April 2012 in SMA Negeri 3 Surakarta. 83 samples had been choosed by simple random sampling. This study use premarital sexual behavior as dependent variable, emotional quotient as independent variable, attitudes about premarital sexual behavior, bad influence of friends and religion as controlled variables. Questionnare to measure all variables had been tested validity and reliability. Samples were analyzed using binary logistic regression with SPSS 17.0. Results: This study shows that by controlling confounding factors, adolescents who have high emotional intelligence maybe lead to good sexual behavior by 6.84 times bigger than adolescents with low emotional intelligence (OR = 6.84; CI 95% = 1.75-26.72; p = 0.006). Conclusion: There is a relationship between emotional intelligence and premarital sexual behavior by controlling confounding factors. High emotional intelligence can reduce bad premarital sexual behavior. Keywords: premarital sexual behavior, emotional intelligence